2021
DOI: 10.1007/s40030-021-00556-7
|View full text |Cite
|
Sign up to set email alerts
|

Are Freight Production Models Transferable between Urban and Suburban Areas? Guiding Model Transfer in Geographically Sprawling Indian Cities

Abstract: Investigating the spatial transferability of freight generation (FG) models is an imperative research need to enable the usage of formerly estimated model parameters in new application contexts with or without the usage of local data. By understanding how to transfer models (and to what extent), planning agencies in large countries like India can save freight survey costs in regions where they lack the institutional capacity and resources. Due to geographically sprawling nature of most of the Indian cities, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Out of the 49 papers, 41 were published in Elsevier journals (83.67%), 3 were published in Springer journals (6.12%), 3 were published in Taylor and Francis journals (6.12%), and 2 were published in SAGE journals (4.08%). The 49 papers can be categorized into four areas: (1) development of disaggregate-level freight demand estimations at seaports [ 5 , 6 ] or urban establishments [ 7 11 ], (2) development of aggregate-level freight generation [ 12 , 13 ] or distribution models [ 14 ], (3) design of establishment-based freight surveys [ 15 , 16 ] and zoning systems [ 17 20 ], (4) analysis of freight transport parking practices [ 21 ], emissions [ 22 , 23 ], expenditure patterns [ 9 , 24 , 25 ], and logistics sprawl [ 26 ]. Since the relevant statistics on freight system performance (e.g.…”
Section: Methods Adopted For the Review And Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 49 papers, 41 were published in Elsevier journals (83.67%), 3 were published in Springer journals (6.12%), 3 were published in Taylor and Francis journals (6.12%), and 2 were published in SAGE journals (4.08%). The 49 papers can be categorized into four areas: (1) development of disaggregate-level freight demand estimations at seaports [ 5 , 6 ] or urban establishments [ 7 11 ], (2) development of aggregate-level freight generation [ 12 , 13 ] or distribution models [ 14 ], (3) design of establishment-based freight surveys [ 15 , 16 ] and zoning systems [ 17 20 ], (4) analysis of freight transport parking practices [ 21 ], emissions [ 22 , 23 ], expenditure patterns [ 9 , 24 , 25 ], and logistics sprawl [ 26 ]. Since the relevant statistics on freight system performance (e.g.…”
Section: Methods Adopted For the Review And Data Collectionmentioning
confidence: 99%
“…To achieve this, Indian Railways is investing heavily on network expansion projects and dedicated freight corridors. The strategic planning of these large-scale projects requires accurate freight demand models [ 24 , 25 , 33 , 34 ].
Fig.
…”
Section: Methods Adopted For the Review And Data Collectionmentioning
confidence: 99%
“…A similar observation was seen in the study by Pani et al (3), where FP models were assessed for transferability. Balla et al (35) also proved that the transferability of FP models is asymmetric. The models were transferable from urban to suburban but not vice versa.…”
Section: Effect Of Sample Size On Transferabilitymentioning
confidence: 96%
“…These models were also assessed for transferability by updating their parameters, and it was found that updating the models improved the extent of transferability. Balla et al ( 35 ) investigated the transferability between urban and suburban regions in India; area-based and employment-based FP models were developed for these regions using OLS. It was found that the models developed for urban regions were transferable to the suburban regions but not vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%